DEVELOPMENT OF ENGLISH POP-UP BOOK MEDIA TO TEACH WRITING SKILL AT JUNIOR HIGH SCHOOL - Aida Nur Ita; Siti Rofi'ah; Istina Atul Makrifah (Wiralodra English Journal, 2024)
This study aims to ensure that the use of Pop-Up Book Media affects the writing abilities of junior high school students. This media focuses with Descriptive Text material to teach writing skill to class VII students. This research use ADDIE model. The sample for this research was class VIIA MTs Sunan Ampel Kediri, totaling 14 students. Data collection was carried out by observation, unstructured interviews with teacher and questionnaires. Data were analyzed using a manual percentage formula. These findings show that the validation percentage of media experts reached 98%, that means "very valid", then the percentage of material validation reached 96%, with means "very valid". The total percentage of student satisfaction questionnaires reached 83.9% which is classified as "Very Satisfied". In conclusion, the use of Pop-Up Book media in learning can increase students' motivation in learning English and increase the creativity of students' in making paragraphs this is immediately effective for developing students' writing skills and the Pop-Up Book learning media is ready to be used by teachers as a learning media.